Annotation on manuscript and their importance in writing and understanding history, Al Faragh, Al samaa: Al Ejazah and AlMunawala annotations as examples - Al–Leheabi, Saleh Muhammad Zeki Mahmood (Al-Adab Journal, 2022)
This research focuses on studying the annotations on the manuscripts, to show their value and how useful they are, considering them as important source of information when studying history and in finding lots of details that might not be available in the conventional resources on which the studies usually depend on. Also these annotations can be in different types and forms, like authorization by the author to someone to teach or use the manuscript (Ejazat), annotations to mark the end of writing (Hard Al Maten), endowment annotations (Waqf), ownership annotations (Tamaluk), hearing annotations (Al Samaa) to show that a person attended a reading of the full manuscript, or handing annotations (AlMunawala) to show a person was handed out the manuscript for use, and other types of annotations that possess huge importance and meanings in re-writing and understanding history. One of the prominent benefits of these annotations is knowing the scientific, cultural and intellectual position of an era, how did the scholars affect the sciences and the life of the public, it also contributes to the knowledge of the names and biographies, dates and details of occasions. The information in the annotations also helped with realizing missing information from some resources, finding the true writers of some other resources and many other historical advantages.